2007
DOI: 10.1093/hmg/ddm218
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of the balanced α/β-globin gene expression in β 654 -thalassemia mice using combined RNAi and antisense RNA approach

Abstract: The beta-thalassemia is associated with abnormality in beta-globin gene, leading to imbalanced synthesis of alpha-/beta-globin chains. Consequently, the excessive free alpha-globin chains precipitate to the erythrocyte membrane, resulting in hemolytic anemia. We have explored post-transcriptional strategies aiming at alpha-globin reduction and beta-globin enrichment on beta(654) (Hbb(th-4)/Hbb(+)) mouse, carrying a human splicing-deficient beta-globin allele (Hbb(th-4)). Lentiviral vectors of short hairpin RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 25 publications
2
37
0
3
Order By: Relevance
“…Xie et al performed an in vivo experiment to knock down a-globin expression by shRNA in a b-thalassemia mouse model. 84 Lentiviral vectors of shRNA targeting a-globin were microinjected into b-thalassemia heterozygous mouse single-cell embryos, and a transgenic mouse was generated that produced 20% to 35% less a-globin. These mice demonstrated sustained phenotypic improvement in red cells with less poikilocytosis, fewer target cells, increased hemoglobin values and red cell counts, and low reticulocyte counts.…”
Section: 79mentioning
confidence: 99%
“…Xie et al performed an in vivo experiment to knock down a-globin expression by shRNA in a b-thalassemia mouse model. 84 Lentiviral vectors of shRNA targeting a-globin were microinjected into b-thalassemia heterozygous mouse single-cell embryos, and a transgenic mouse was generated that produced 20% to 35% less a-globin. These mice demonstrated sustained phenotypic improvement in red cells with less poikilocytosis, fewer target cells, increased hemoglobin values and red cell counts, and low reticulocyte counts.…”
Section: 79mentioning
confidence: 99%
“…Although a recent study has demonstrated slight phenotypic improvements in transgenic mice expressing short-hairpin RNA targeting α-globin, the authors concede that this is not applicable in a therapeutic setting. 17 In this study, we report that siRNA can be used to reduce expression of a highly expressed gene such as α-globin at both the RNA and protein level. To the best of our knowledge, this is the first study demonstrating definitive reduction of endogenous globins mediated directly with siRNA without any DNA intermediates.…”
Section: Sirna Mediated Reduction Of α α-Globin In Erythroid Progenitmentioning
confidence: 99%
“…Há uma tentativa de compensação pela medula óssea, com aceleração da produção de eritrócitos, porém insuficiente para [125][126][127] .…”
Section: Fisiopatologiaunclassified